Pengaruh Media TAKALINTAR terhadap Keterampilan Operasi Hitung Perkalian pada Siswa Kelas IV SDN 066657 Martubung - Silvia Anggraeni Br Sitepu; Melyani Sari Sitepu (Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to determine the effect of multiplication media (smart multiplication table) on students' multiplication arithmetic operation skills. This research uses a type of quantitative research which is used with the Pre Experimental Design design in the form of One Group Pretest-Posttest Design. This design has a pretest before being given treatment. . so that in this study the results of the treatment can be known more accurately because it can be compared with the conditions before being given treatment (treatment). The research subjects were class IV students at SDN.000675 Mertubung which consisted of one class with a population of 21 students. The research sample consisted of 21 people taken from the population using saturated sampling. The research instrument used was a test in the form of multiple choices with a total of 15 questions. The validity and reliability of the instrument was tested using the Software Statistical Package For The Social Sciences (SPSS). The analytical technique used was the t test with the hypothesis H0 = rejected and Ha = accepted. Based on the results of calculating the t test statistics, it is known that tcount is 8.583 and ttable (sign = 0.000) with a df of 20 is 2.093. At a significance level of 5% (8.583 2.093) and has a significance value of less than 0.05 (p = 0.000 0.05). From this comparison it was decided that Ha was accepted and H0 was rejected, this means that there was an influence from the pretest before being given treatment to the posttest after being given treatment. So it can be concluded that Takalintar Media influences the multiplication arithmetic operations skills of class IV SDN students. 066657 Martubung.